Decoding Galactic Merger Histories - Eric F. Bell; Antonela Monachesi; Richard D’Souza; Benjamin Harmsen; Roelof S. de Jong; David Radburn-Smith; Jeremy Bailin; Benne W. Holwerda (Galaxies, 2017)
Galaxy mergers are expected to influence galaxy properties, yet measurements of individual merger histories are lacking. Models predict that merger histories can be measured using stellar halos and that these halos can be quantified using observations of resolved stars along their minor axis. Such observations reveal that Milky Way-mass galaxies have a wide range of stellar halo properties and show a correlation between their stellar halo masses and metallicities. This correlation agrees with merger-driven models where stellar halos are formed by satellite galaxy disruption. In these models, the largest accreted satellite dominates the stellar halo properties. Consequently, the observed diversity in the stellar halos of Milky Way-mass galaxies implies a large range in the masses of their largest merger partners. In particular, the Milky Way’s low mass halo implies an unusually quiet merger history. We used these measurements to seek predicted correlations between the bulge and central black hole (BH) mass and the mass of the largest merger partner. We found no significant correlations: while some galaxies with large bulges and BHs have large stellar halos and thus experienced a major or minor merger, half have small stellar halos and never experienced a significant merger event. These results indicate that bulge and BH growth is not solely driven by merger-related processes.